Pengaruh Drama Korea Terhadap Life Style dan Konsumsi ( Studi Kasus Mahasiswa Universitas Islam Negeri Sumatera Utara) - Ria Septiana; Riska Arianti Nasution; Dini Lestari (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
This study aims to determine the influence of Korean dramas on lifestyle and consumption. This study uses a quantitative method with data collection through a questionnaire (questionnaire) and data analysis using the method of determination (R). The results showed that there was an influence of Korean drama on the lifestyle and consumption of North Sumatra State Islamic University students by 36% (coefficient of determination). Meanwhile, 63% of the other influences on student lifestyle and consumption are influenced by other variables not included in this study